The Development Process of Human Machine Interface of Plant Protection System of a Small Modular Reactor - Suryono, Tulis Jojok; Santoso, Sigit; Maerani, Restu; Pratama, Pandhu Ardita Dharma (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2023)
The Plant Protection System (PPS), which consists of Reactor Protection Systems (RPS) and Engineered Safety Actuated Systems (ESFAS), is one of the most important safety systems in nuclear reactors, including Small Modular Reactors (SMRs). The RPS generates a signal to trip the reactor if the measured reactor parameters exceed the trip setpoint, and then the ESFAS is actuated to mitigate the consequences of the accident by minimizing fuel damage and radioactivity release into the environment. Therefore, a comprehensive Human-Machine Interface (HMI) is essential for monitoring and controlling the PPS to ensure its reliability and enhance the operators' situational awareness. This study discusses the development process of the HMI for the digital PPS of an SMR. In this study, various standards, guidance, and design criteria for PPS and HMI are incorporated and applied to ensure that the proposed design meets the required level of reliability. In the first stage, the proposed design is intended for assessing the functionality and reliability of the PPS. Moreover, in the future, it will play an essential role in the design phase of the HMI for the PPS of an SMR in Indonesia.